Faktor-faktor yang Menyebabkan Target Indeks Pembangunan Manusia Sulit Tercapai: Sebuah Analisis terhadap Lingkungan Strategis - Iis Sandra Yanti; Muhammad Ilham; Khasan Effendy; Sampara Lukman (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
Human Development Index (HDI) is still used for determining the quality of human life in local government. In local government, specially in industrial region, HDI is to hard to be achieved. Bekasi regency as the biggest industrial region of the South-East Asia also has same problem about achieving HDI target annually. With qualitative method, this research tries to identify factors that causing HDI target of Bekasi Regency is not achieved in 2012-2017 period. Some results shows that the factors are natural environment, social environment, and task environment.